The Effect of Financial Knowledge and Financial Attitude on Credit Card Usage Among Credit Card Holders in General Santos City - Eslera, Mae Flor L.; Dindang, Ronairah D. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the influence of financial knowledge and financial attitude on credit card usage among credit card holders in General Santos City, Philippines using a quantitative descriptive-correlational design. A total of 420 respondents completed a structured survey based on a five-point Likert scale. Financial knowledge was measured through interest rates, payment readiness, and fee awareness, while financial attitude was assessed using risk tolerance, budget discipline, and impulse control. Credit card usage was evaluated through fraud and security awareness, payment behavior, and debt accumulation. Descriptive analysis revealed very high levels of financial knowledge, financial attitude, and credit card usage among respondents. Pearson correlation and multiple regression analyses indicated strong, statistically significant positive relationships between financial knowledge and credit card usage, and between financial attitude and credit card usage. Financial knowledge explained 63% of the variance in credit card usage, and financial attitude accounted for 70%. To investigate the moderating effects of demographic variables—age, sex, marital status, education, employment status, industry, and income—normality tests using Shapiro-Wilk and Kolmogorov-Smirnov methods were performed. Due to non-normal data, bootstrap mediation analysis was conducted, showing no significant mediation by demographic factors. The null hypotheses regarding the effects of financial knowledge and financial attitude were rejected, confirming their significant influence on credit card usage. However, the null hypotheses for demographic moderation were accepted. The findings highlight the importance of enhancing financial knowledge and fostering responsible financial attitudes to promote mindful credit card use. Future studies should explore other potential mediators such as financial anxiety, self-control, and access to financial education.